Prescription patterns and therapeutic gaps among persons with epilepsy in Southwestern Nigeria - Ogunjimi, Luqman; Osalusi, Bamidele; Fagbemi, Ayotomiwa; Oyenuga, Ibironke; Ojini, Fedora; Collins, Samuel; Elegbede, Oluwatosin; Oladele, Olayinka; Fehintola, Fatai (Frontiers in Pharmacology, 2024)
Introduction: Pharmacotherapy with antiseizure medications (ASMs) has been a cornerstone for achieving long-term remissions in persons with epilepsy (PWEs). This study aims to determine the prescription patterns and treatment gaps (TGs) among PWEs. Methods: Accordingly, a descriptive cross-sectional study was conducted with 940 PWEs aged ≥18 years having clinically confirmed diagnosis of epilepsy based on the International League Against Epilepsy (ILAE) criteria. At a scheduled interview with each participant, a previously established questionnaire was used to obtain clinical information relating to epilepsy in terms of the age of onset, etiology, duration of epilepsy, frequency, types, and number of ASMs used. Results: There were fewer male participants [445 (47.4%) vs. 495 (53.6%)] than females, with a higher mean age of onset [(35.19 ± 21.10 vs. 31.58 ± 20.82 years; p = 0.009]. The medication characteristics showed that 336 (35.7%) of the 940 PWEs recruited were not on any ASMs, whereas the remaining 604 (64.3%) patients were on ASMs, with 504 (83.4%) on monotherapy vs. 100 (16.6%) on polytherapy. The PWEs on ASM monotherapy had a higher mean age [40.92 ± 19.40 vs. 33.61 ± 16.51 years; p < 0.001] and higher mean age of onset [34.47 ± 21.80 vs. 25.39 ± 19.78 years; p < 0.001] than those on polytherapy. Furthermore, there were more persons on ASM monotherapy among the participants with seizure duration < 2 years [251 (87.5%) vs. 36 (12.5%)] and seizure duration > 2 years [253 (79.8%) vs 64 (20.2%)]. Conclusion: The majority of the participants receiving ASMs were on monotherapy, with carbamazepine being the most frequently prescribed medication. Furthermore, about a third of the participants had TGs; therefore, healthcare providers should focus on alleviating the TGs among PWEs.